Новые и малоизвестные слепняки (Heteroptera, Miridae) фауны Туркменской и Киргизской ССР - Пучков, В.Г. (Вестник зоологии, 1976)
The new species are described: Phylocoris moira L i n n. (female), Ph. haloxyli Putshkov sp. n., Ph. sunti Putshkov sp. n., Megacoelum pistaceae Putshkov sp. n. and Lopidodenus bipunctatus Putshkov sp. n., Lopidodenus albidus (Reuter,
1903) comb. n.=Lopidodenus ogivus Putshkov, 1974, syn. n., Voruchiella P o p p i u s,
1912=Itupano W a g n e r, 1957, syn. nov. A key of three species of genus Voruchiella P o p p. is given.